Behaviour and energy budget of wintering geese in the Lower Rhine area of north Rhine-Westphalia, Germany - Mooij, J H (Wildfowl, 1992)
The most important activity of wintering geese in the Lower Rhine area is feeding, which accounts for approximately 55% of a 24-hour day. Almost 40% of this feeding takes place at night. Sleeping occupies about 30% of a 24-hour day, more than 80% of which takes place during the hours of darkness distributed among 4-5 sleeping bouts of 1-1 1/4 hours each. The remainder is spent drinking/preening (about 8%) and in bouts of alertness, social behaviour and flying (about 2% each). The average flight distance of the geese between roosts, roost and feeding site and between feeding sites is 5.1 km, the average flight velocity is 43.8 km/h. A White-fronted Goose (mean weight 2.4 kg) requires about 1500 g fresh weight (300 g dry matter) and a Bean Goose (mean weight 3.5 kg) about 1950 g fresh weight (390 g dry matter) of grass daily respectively. A gooseday (gd) is therefore a variable quantity, depending on the species. The feeding intensity measured in goosedays per hectare (gd/ha) only has validity for a specific goose species. The disturbance of geese promotes activities with a high energy consumption and reduces all activities that save energy. In addition every disturbance prevents food intake and thereby energy intake and fat deposit accumulation. Nocturnal feeding and roosting on land are common for the geese of the Lower Rhine area and maybe are also more common for geese feeding mainly on grassy vegetation at other wintering sites than has been assumed. Both phenomena can be explained by the high energy costs of roosting on cold water during the night (about 1000 kJ, i.e. almost 25 g of body fat).